2016
DOI: 10.11604/pamj.2016.25.117.9827
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with post-cesarean stillbirth in 12 hospitals in Benin: a cross-sectional

Abstract: IntroductionIn spite of free caesarean section applied in Benin since 2009, high rates of stillborn babies continue to be recorded. This study aimed to determine the factors associated with post-caesarean stillborn in Benin.MethodsCross-sectional study that covered all women who have delivered by caesarean from December 2013 to February 2014 in twelve hospitals chosen by simple random selection in each of the twelve departments of Benin. Data collected by chart review have been analyzed using the statistical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Studies conducted in Denmark and West Africa also demonstrated that cesarean section is a predictor of stillbirth [39,40]. This report implied that health caregivers working on MCH should take into consideration the possible risk of cesarean section while assessing the risk of pregnancy at the ANC clinic.…”
Section: Plos Onementioning
confidence: 80%
“…Studies conducted in Denmark and West Africa also demonstrated that cesarean section is a predictor of stillbirth [39,40]. This report implied that health caregivers working on MCH should take into consideration the possible risk of cesarean section while assessing the risk of pregnancy at the ANC clinic.…”
Section: Plos Onementioning
confidence: 80%
“…Our stillborn rate is 11.3% among all cesarean mothers. This rate is in the interval of stillborn rates associated with cesarean section [37] [38].…”
Section: Discussionmentioning
confidence: 96%
“…This is similar to what was found in other studies. 9,[20][21][22] This causes a delay for women to reach Mulago hospital which increases the risk of stillbirth. In addition, women who develop complications during labor are more likely to be referred and have an increased risk of delivering stillbirths.…”
Section: Discussionmentioning
confidence: 99%
“…Women's conditions may not be correctly identified and managed or the required intervention may not be given in time. 9,10 In some settings, cesarean section coverage is low 6 due to a shortage of trained healthcare personnel and shortage of theatre equipment and supplies. Sometimes women are required to pay for medications and supplies, which may delay timely interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation